Vera. Set 3 [videorecording (DVD)] - Cleeves, Ann ([publisher not identified], 2014)
This is a compelling mystery series, inspired by Ann Cleeves' bestselling novel. Patrolling her patch of northeast England, Vera resolutely pursues the truth in cases of murder, kidnapping, and blackmail. While her manner is sometimes caustic, her single-mindedness gets results.